Wrongful Omission as a Condition for Tort Liabilities - Buletsa, Sibilla; Hrinko, Svitlana; Hrinko, Ruslan; Anikina, Halyna (Journal of Legal Studies, 2020)
As omission of a person is a certain manifestation of his/her internal will from outside. Exactly through inactivity, the internal will of a person materializes due to which a person becomes a participant of public relations. At the same time in the absence of external expression of will inactivity of a person can not cause the occurrence of legal consequences, in particular, to be examined as a reason of origin of tort liabilities. If a person enacted because of negligence or poor awareness, it should be defined: whether a person knew or had to know about the necessity to perform a certain action. Accordingly, if a person possessed such knowledge this form of behavior will be treated as guilty omission, if not – this is an example of innocent omission. Responsibility for illegal omission can arise only when appropriate persons are included in the system of civil and legal relationships, thus are the subjects of civil relations. Damage caused by “reflexive movements” testifies the carelessness of a person to his/her behavior, which reflects his/her will. Therefore, such behavior of a person is considered to be wrongful.